Gauging trauma-informed pedagogy in higher education: a UK case study - Bitanihirwe, Byron; Imad, Mays (Frontiers in Education, 2023)
Introduction A substantial amount of evidence suggests a negative association between traumatic experiences and mental health among primary and secondary school students. These vulnerable students are at an increased risk of academic, social, and emotional problems. However, there is limited evidence on the connection between traumatic experiences and student mental health in higher education, especially regarding trauma-related content in classrooms. This study aims to explore students’ experiences with traumatic material in a UK university setting and to understand educators’ perceptions of trauma-informed pedagogy. Methods Eight students from the University of Manchester and seven educators (from the humanities and social sciences departments) participated in one-on-one semi-structured interviews. The analysis adopted an inductive thematic approach. Results Four major themes emerged from the interview data: Inclusion and delivery of trauma-related content in higher education; Effects of trauma-related content on class attendance; Availability of support systems for handling trauma-related content; Perceptions on trauma-informed education. Discussion The implications of this study for future research and current teaching practices are discussed. Recommendations are provided for teaching sensitive material. Limitations of this study, such as sample size and demographics, are acknowledged. Additionally, a conceptual framework for trauma-informed pedagogy is introduced, laying the groundwork for an upcoming concept paper.